2010
DOI: 10.3748/wjg.v16.i8.982
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost impact of intravenous proton pump inhibitor use in non-ICU patients

Abstract: This study highlights the over-utilization of IV PPIs in non-intensive care unit patients. Restriction of IV PPI use for justified indications and route of administration is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 16 publications
1
32
4
1
Order By: Relevance
“…Only a small number of studies have examined the effectiveness of this prophylactic attitude in non-ICU patients [9,15], as well as its cost impact [16,17], and none were proper prospective controlled studies. These studies have shown a higher incidence of bleeding, but there were major differences in the populations considered in each one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a small number of studies have examined the effectiveness of this prophylactic attitude in non-ICU patients [9,15], as well as its cost impact [16,17], and none were proper prospective controlled studies. These studies have shown a higher incidence of bleeding, but there were major differences in the populations considered in each one.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown a higher incidence of bleeding, but there were major differences in the populations considered in each one. Some of those particular characteristics included patients initially admitted to ICUs [6,15], patients submitted to major surgeries [16,17], including organ transplant [6], and patients with prolonged times of admission (more than 14 days) [6]. All these are relevant factors which are not present in typical medical patients, admitted to internal medicine wards.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Other similar studies have also concluded that of those patients who were prescribed a proton pump inhibitor, either during their stay at the hospital or upon discharge, a significantly large percentage were guideline non-compliant. [2,3,4,5,6,7] A recent study performed in the state of Maryland incorporated two different hospitalist groups: academic and non-academic hospitals. All PPI prescriptions dispensed at the hospitals were investigated in accordance to FDA guideline compliance.…”
Section: Non-compliant Ppi Prescriptionsmentioning
confidence: 99%
“…Those involved in the study found that the total cost in a year of inappropriate PPI use, whether it be non-compliant indication or inappropriate documentation, was $233,994 [10] based on over-the-counter costs and $1,566,252 [10] based on average whole sale price costs. Another clinical study geared toward the cost impact of the overuse of proton pump inhibitors in non-ICU patients found that an annual cost savings of over $35,000 [6] could be possible if precautions were set in place to stop the non-compliant prescribing of PPIs.…”
Section: Economic Effect Of Ppi Overusementioning
confidence: 99%
“…According to one US study conducted in a university hospital, the inappropriate PPIs use contributed to potential increased cost of USD 37000 per year without involving the cost associated with potential risks of unnecessary therapy (Belfield et al, 2017). The cost burden associated with PPIs misuse can be minimized with the pharmacist intervention in reviewing prescribing orders for proper indications, route of administration and appropriate timing for switching from oral to intravenous (IV) preparations (Nasser et al, 2010). Moreover, it was highlighted that the physicians should advise their patients to elude the unnecessary use of PPIs because of its safety concerns particularly in the patients who are more prone to osteoporotic fracture (Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%